Dampak Dhuafa Mart Dalam Pemberdayaan Ekonomi Masyarakat - Mairiza, Diany; Assyifa, Zubaidah; Zakir, Muhammad; Khairi, Rifqil; Winario, Mohd; Lismawati, Lismawati (Journal of Community Sustainability, 2024)
This community service was conducted for Dhuafa Mart retail business owners in Air Tiris, Kampar Subdistrict, Kampar Regency. The aim of this community service was to determine the impact of managing Dhuafa Mart on empowering the local economy and to assess the success level of this community service activity. The methods used in this community service included counseling, presentations, and discussions. The results of the service showed that: The community service program was well-organized and proceeded smoothly according to the planned activities. The conclusions from this service were as follows: there were several impacts from the Dhuafa Mart program on community economic empowerment, namely; (1) Enhancement of Economic Independence, (2) Job Creation, (3) Increased Income, (4) Expanded Access and Networks, (5) Encouragement for Sustainability. The Dhuafa Mart program also demonstrated a significant impact on increasing the economic independence of the underprivileged community, providing them with opportunities for a better life and positively contributing to local economic development.